Fostering Self-Authorship Through Work Integrated Learning in University Tourism Programs: A Missed Opportunity?. Issue 4 (1st October 2020) - Caldicott, Julia; Wilson, Erica; Donnelly, James F.; Edelheim, Johan R.
ABSTRACT: Work integrated learning (WIL), in its various forms, continues to be a central element of university tourism programs. Internships, the most common form of WIL, provide opportunities for both personal and professional development. This article presents findings of a content analysis of WIL programs in Australian tourism, hospitality and events (TH&E) undergraduate degrees. Publicly available unit/subject guides were gathered through an internet-based review. This analysis of secondary data identified that the majority of WIL curricula in the Australian university TH&E programs focus on career development, followed by academic achievement and thirdly, personal development. It is argued that the opportunity to facilitate students' personal growth and the achievement of advanced learning outcomes through WIL is not being fully realized. Through the lens of 'self-authorship', meaning in this case, the student's use of their internal voice to guide their beliefs, identity and relationships, this paper explores the opportunities for WIL programs to be (re)designed to meet industry needs while also facilitating the individual, personal development of future tourism, hospitality and events leaders.